A customizable anthropomorphic phantom for dosimetric verification of 3D‐printed lung, tissue, and bone density materials. Issue 1 (2nd December 2021) - Tino, Rance Bolislis; Yeo, Adam Unjin; Brandt, Milan; Leary, Martin; Kron, Tomas
Abstract: Purpose: To design and manufacture a customized thoracic phantom slab utilizing the 3D printing process, also known as additive manufacturing, consisting of different tissue density materials. Here, we demonstrate the 3D‐printed phantom's clinical feasibility for imaging and dosimetric verification of volumetric modulated arc radiotherapy (VMAT) plans for lung and spine stereotactic ablative body radiotherapy (SABR) through end‐to‐end dosimetric verification. Methods: A customizable anthropomorphic phantom slab was designed using the CT dataset of a commercial phantom (adult female ATOM dosimetry phantom, CIRS Inc.). Material extrusion 3D printing was utilized to manufacture the phantom slab consisting of acrylonitrile butadiene styrene material for the lung and the associated lesion, polylactic acid (PLA) material for soft tissue and spinal cord, and both PLA and iron‐reinforced PLA materials for bone. CT images were acquired for both the commercial phantom and 3D‐printed phantom for HU comparison. VMAT plans were generated for spine and lung SABR scenarios and were delivered as per departmental SABR protocols using a Varian TrueBeam STx linear accelerator. End‐to‐end dosimetry was implemented with radiochromic films, analyzed with gamma criteria of 5% dose difference, and a distance‐to‐agreement of 1 mm, at a 10% low‐dose threshold by comparing with calculated dose using the Acuros algorithm of the Eclipse treatment planning system (v15.6). Results: 3D‐printed phantom inserts were observed to produce HU ranging from –750 to 2100. The 3D‐printed phantom slab was observed to achieve a similar range of HU from the commercial phantom including a mean HU of –760 for lung tissue, a mean HU of 50 for soft tissue, and a mean HU of 220 and 630 for low‐ and high‐density bone, respectively. Film dosimetry results show 2D‐gamma passing rates for lung SABR (internal and superior) and spine SABR (inferior and superior) over 98% and 90%, respectively. Conclusions: The end‐to‐end testing of VMAT plans for spine and lung SABR suggests the clinical feasibility of the 3D‐printed phantom, consisting of different tissue density materials that emulate lung, soft tissue, and bone in kV imaging and megavoltage photon dosimetry. Further investigation of the proposed 3D printing techniques for manufacturability and reproducibility will enable the development of clinical 3D‐printed phantoms in radiotherapy.